Monitoring Fuel Dilution of Diesel Engine Lubricant Oil by Ultraviolet Fluorescence Spectroscopy. Issue 1 (1st February 2022) - Li, Jing; Tian, Hongxiang; Yunling, Sun; Huang, Heng; He, Wei
Abstract: Fuel contamination is a common problem in lubricating oil contamination. Generally, methods such as gas chromatography can be used, but the experimental process is more complicated. Fluorescence spectroscopy analysis has the advantages of fast detection speed and high sensitivity. Applying it to fuel dilution analysis can simplify the analysis process and enable rapid and accurate quantitative analysis. A certain type of fluorescence spectrophotometer was used to analyze and monitor lubricating oil containing different proportions of diesel oil. The fluorescence sensitive band was found, and the corresponding relationship between different lubricating oil content and the height and peak area of the fluorescence characteristic peak was analyzed.